Policy options for increasing crop productivity and reducing soil nutrient depletion and poverty in Uganda - Nkonya, Ephraim M.; Pender, John L.; Kaizzi, Crammer; Kato, Edward; Mugarura, Samuel (International Food Policy Research Institute, 2005)
This study was conducted with the main objective of determining the linkages between poverty and land management practices in Uganda. The study used the 2002/03 Uganda National Household Survey (UNHS) and more focused data collected from a sub-sample of 851 households of the 2002/03 UNHS sample households. We found that farmers in Uganda deplete about 1.2 percent of the nutrient stock stored in the topsoil per year, which leads to a predicted 0.31 percent reduction in crop productivity. The value of replacing the depleted nutrients using the cheapest inorganic fertilizers is equivalent to about 20 percent of household income obtained from agricultural production. Econometric analysis of the survey results provides evidence of linkages between poverty and land management practices. Land investments increase agricultural productivity and income and conserve natural resources. Many inputs and land management practices increase crop production per acre. We observed an inverse farm size – crop productivity relationship but a negative association of farm size and per capita income. Education of female household members has generally a limited impact on land management, while male education is associated with greater use of inorganic fertilizer. Both female post-secondary and male primary and secondary education are associated with higher crop productivity. Larger families use more erosive practices but realize higher value of crop production per acre but have lower per capita income. Access to financial capital, markets and roads has limited effect on land management. However, access to financial capital and non-farm opportunities increase crop productivity and per capita household income and access to roads contributes to higher per capita household income and less soil nutrient depletion. These results support the Uganda government poverty reduction strategy through building rural roads, and increasing access to financial capital and non-farm opportunities. Both the traditional and the new agricultural extension program increase use of fertilizer and crop productivity, suggesting that investment in extension services could significantly contribute to agricultural modernization and poverty reduction. The results suggest the need to give incentives for technical assistance programs to operate in remote areas, where access to extension services is limited. Perennial crop producers deplete soil nutrients more rapidly, implying the need to promote measures to restore soil nutrients in perennial (especially banana) production areas. We find no significant differences in crop productivity or income per capita associated with differences in land tenure systems. Our findings suggest that customary land tenure, which is the most common form of tenure, is not a constraint to improvements in land productivity or use of sustainable land management. Overall, our results provide general support for the hypothesis that promotion of poverty reduction and agricultural modernization through technical assistance programs and investments in infrastructure and education can improve agricultural productivity and help reduce poverty. However, they also show that some of these investments do not necessarily reduce land degradation, and may contribute to worsening land degradation in the near term. Thus, investing in poverty reduction and agricultural modernization is not sufficient to address the problem of land degradation in Uganda, and must be complemented by greater efforts to address this problem.